Pseudomonas aeruginosa meningitis in an elderly - A case report - Kamath, Sangita Deepak; Gupta, Satish Chandra; Sunder, Ashok (Indian Journal of Case Reports, 2020)
Community-acquired meningitis caused by Pseudomonas aeruginosa is rare and has a very high mortality rate. We describe the case of a 74-year-old well-controlled diabetic female who spontaneously developed Pseudomonas meningitis causing altered sensorium, confusion, and irritability. Cerebrospinal fluid grew P. aeruginosa sensitive only to meropenem. Blood cultures were sterile. Noncontrast computed tomography of the brain showed age-related cortical atrophy. The patient responded well to 15 days of broad-spectrum antimicrobial therapy with intravenous meropenem and levofloxacin. This is the first reported case of spontaneous community-acquired P. aeruginosa meningitis in a patient with no history of head trauma, neurosurgery, or lumbar spinal puncture.